1971
DOI: 10.1161/01.str.2.3.213
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Stroke Rehabilitation

Abstract: Quantitative and semiquantitative methods have been used to evaluate the clinical improvement of 62 patients with completed stroke who were admitted to a rehabilitation hospital. Improvement in motility and leg strength on the paretic side was minimal and was not influenced by facilitation exercise techniques. Observed changes in strength and motility occurred to about the same degree on both the nonparetic and paretic sides. Patients who had a short interval between onset of stroke and admission to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

1972
1972
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(25 citation statements)
references
References 0 publications
3
22
0
Order By: Relevance
“…This study, like others before it (4,11,13,14,23), demonstrated that strength increases over time in hemiparetic stroke patients. This study, however, went a step further.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This study, like others before it (4,11,13,14,23), demonstrated that strength increases over time in hemiparetic stroke patients. This study, however, went a step further.…”
Section: Discussionsupporting
confidence: 85%
“…Over the past 10 years, an increasing number of reports have been published in which the muscle strength of patients with stroke has been measured quantitatively by hand grip (3,4), fixed (5-7), hand-held (8)(9)(10)(11)(12)(13), or isokinetic dynamometers (3,(14)(15)(16)(17)(18)(19)(20)(21)(22). What is known from these reports is that: (a) strokes do cause weakness, not only of the side contralateral to the brain lesion but also of the side ipsilateral to the lesion (3,14,15,17,18); (b) all muscle groups are not affected equally, and the relative involvement of specific muscle groups may differ from that traditionally expected (6,13); (c) normal mechanisms that alter muscular strength such as length/tension and force/velocity relationships may explain, in part, the limitations in strength noted under specific conditions (18)(19)(20); (d) significant relationships such as normally exist between muscle strength and independent variables, such as age, weight, and gender, are maintained on the nonparetic but not on the paretic side (12); (e) muscle strength is related to function (3,10,21,22); (0 muscle strength tends to increase with time following a CVA (4,11,13,14,23); and (g) strength soon after stroke is a predictor of strength at a later time (4,…”
mentioning
confidence: 99%
“…Key Words: Stroke—Motor recovery—Rehabilitation—Outcome. (2,4,(6)(7)(8), cognitive deficits (2,8), urmary mcontinence (9), mterval from stroke to rehabilitation (2,10), and postural balance (5,(11)(12)(13) also are important.…”
Section: Motor Impairment As a Predictor Of Functional Recovery Andmentioning
confidence: 99%
“…4,6 Early mobilization is expected to be essential, but few studies have focused on early activation, and only one experimental and two quasi-experimental studies focusing on early activation reported positive effects. 13,15,16 The results of many studies have been restricted by small samples, late inclusion of patients, a selected stroke population, and/or outcome measures with unknown validity or reliability, unblinded studies, or studies without an experimental design. [17][18][19] On the basis of these studies it is impossible to document with certainty that the acute medical treatment is of benefit.…”
mentioning
confidence: 99%